Scenarios—using the complexity frame of reference to inform the construction of available futures in the possibility space - Byrne, David Sidney (Frontiers in Complex Systems, 2024)
The global socio-ecological system in the era of the capitalocene -the world system created by the use of fossil fuels to provide energy for the development of a growth oriented capitalist logic in all areas of production and consumption -is facing a set of interwoven sub-system crises which come together to make it extremely unlikely that the global system can continue in its present form. The whole system is in a state of crisis -a system state which cannot continue to exist and in which the system must either return to a previous system state -be resilient in the common usage of that word to mean "bouncing back" -or be transformed into a new relatively long lasting but qualitatively different state. The most evident whole system crisis if of course a product of the impending climate transformation contingent upon global warming but there are related crises of increasing social inequality, of demographic structures, of health and care systems, of fiscal and public expenditure processes, and of urban systems in an urbanized world. These are all interwoven to constitute a polycrisis across the global socio-ecological world system. They are also manifest at all geographical levels and in particular the level of city regions which in a predominantly urbanized world are crucial levels for administration and action. The complex realist frame of reference can be used to inform the development of scenarios of the available alternative system states in the path dependent possibility space. We have to start from where we are to get to where we want to go. Scenarios are not just descriptions of possible futures but also include a specification of the actions -the drivers -which shape the creation of specific kinds of futures in those available to us. The construction of scenarios should be done through a process of action research involving a dialogue among system scientists, key actors in governance systems, and civil society. Co-production of knowledge as a guide to action is essential.